1999
DOI: 10.1046/j.1365-2222.1999.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the relationship between childhood asthma and respiratory infection during gestation

Abstract: This study has shown an association between presentation with respiratory infection during gestation and childhood asthma. The results were not affected by the other independent variable factors studied and therefore provide some evidence to support the theory that respiratory viruses may be implicated in the aetiology of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Seven cohort studies, [1,1216,19] 2 case–control studies, [17,18] and 1 cross-sectional study [2] were included in the analysis. Publishing year ranged from 1999 to 2015.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven cohort studies, [1,1216,19] 2 case–control studies, [17,18] and 1 cross-sectional study [2] were included in the analysis. Publishing year ranged from 1999 to 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [2,12,13,15,17] used questionnaires (of which 3 studies [13,15,17] specified “report of physician-diagnosed asthma or eczema”), and 5 [1,14,16,18,19] studies diagnosed by physician or medical record review. Participant age range varied between studies, including 2 to 5 years, [14] 15 to 17 years, [15] 3 to 14 years, [2] and 5 to 16 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms behind such protections are being investigated, and maternal Toll-like receptor (TLR) signaling has recently been shown to be an important participant (22). Maternal infections with parasites (23), viruses (24), and exposure to viral antigens (25) during gestation have also been recently shown to modulate the immune response in the offspring in both helpful and harmful ways. These data, along with observations from probiotic intervention studies (to be discussed in detail below), show that maternal microbial exposure during gestation may lead to long-term health consequences for the offspring by influencing fetal immune development.…”
Section: Gestationmentioning
confidence: 99%
“…For example, we previously showed that immune responses can contribute to the severity of pulmonary inflammatory responses in Mycoplasma respiratory disease, while at the same time preventing dissemination of the infection to extrapulmonary sites (10). Furthermore, immunity is central to the development of respiratory allergies and asthma (11,12), in which infectious agents and environmental factors appear to affect the susceptibility or severity of these conditions (13)(14)(15)(16)(17)(18)(19)(20)(21). Thus, immunity can have both beneficial and detrimental effects on respiratory disease, and it is critical to understand the factors that influence immune responses that can impact the progression and prevention of respiratory diseases.…”
mentioning
confidence: 99%